2008
DOI: 10.1097/jto.0b013e318186a88d
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Trial of Gefitinib Monotherapy in Chemotherapy-Naïve Patients of 75 Years or Older with Advanced Non-small Cell Lung Cancer

Abstract: Gefitinib monotherapy is effective and relatively well tolerated in chemotherapy-naïve elderly patients with advanced NSCLC. Gefitinib has potential as a first-line therapeutic option in elderly patients with advanced NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 28 publications
(27 reference statements)
1
28
0
Order By: Relevance
“…All of these trials reported an increase in ORR (13-43%) and PFS (4-5.9 months). Additional EGFR-mutational analyses revealed that the benefit was consistently highest in patients with tumors harboring the activating EGFR gene mutations [36,[43][44][45][46] [47][48][49][50]. Recently published meta-analyses consistently confirmed that EGFR mutations predict response to EGFR TKI with much higher sensitivity (0.78; 95% confidence interval (CI) 0.74-0.82) than do EGFR gene copy numbers or EGFR expression levels [51].…”
Section: Afatinib -An Irreversible Erbb Family Blockermentioning
confidence: 75%
See 1 more Smart Citation
“…All of these trials reported an increase in ORR (13-43%) and PFS (4-5.9 months). Additional EGFR-mutational analyses revealed that the benefit was consistently highest in patients with tumors harboring the activating EGFR gene mutations [36,[43][44][45][46] [47][48][49][50]. Recently published meta-analyses consistently confirmed that EGFR mutations predict response to EGFR TKI with much higher sensitivity (0.78; 95% confidence interval (CI) 0.74-0.82) than do EGFR gene copy numbers or EGFR expression levels [51].…”
Section: Afatinib -An Irreversible Erbb Family Blockermentioning
confidence: 75%
“…Anyhow, given that in many trials the HR for OS was slightly in favor of first-line EGFR TKI [52] and that the quality of life was maintained for much longer in TKI-treated patients [59], it is concluded that patients with EGFR-mutant tumors gain the greater benefit when TKIs are given early during the natural course of the disease [56]. Especially patients who are older or have a poor performance status will derive a greater benefit from first-line EGFR TKIs [46,60]. These trials also clearly show that proper selection of patients is absolutely crucial for treatment with EGFR-targeted agents in both directions.…”
Section: Egfr Mutation-positive Lung Adenocarcinoma -A Distinct Subsementioning
confidence: 99%
“…EGFR mutations were detected in tumor tissues from seven patients, of which five had partial responses. Four patients had possible interstitial lung disease including two treatment-related deaths [29]. A phase II randomized trial, named INVITE (Iressa in NSCLC versus Vinorelbine Investigation in The Elderly), compared gefitinib with vinorelbine as first-line treatment of elderly advanced NSCLC patients.…”
Section: Clinical Studies Of Egfr-tki In Elderly Patientsmentioning
confidence: 99%
“…Interestingly, several previous clinical trials have examined the efficacy of gefitinib as a first-line treatment for elderly patients with NSCLC harboring sensitive EGFR mutations [15][16][17][18][19][20][21]. Their results suggest that first-line gefitinib is preferable to standard therapy in elderly patients.…”
Section: Introductionmentioning
confidence: 95%